ISSUES OF TEXT LINGUISTICS (International Conference on Modern Science and Scientific Studies, 2025)
Text linguistics is a subfield of linguistics that focuses on the study of texts as communicative events. This article explores the key issues within text linguistics, including coherence, cohesion, intertextuality, and the role of context in understanding texts. By examining these elements, we can gain insights into how texts function in communication, how meaning is constructed, and the implications for language teaching and computational linguistics.